Implementasi Undang-Undang Ketenagakerjaan dalam Memberikan Perlindungan Hukum Terhadap Eksploitasi Pekerja Anak di Kawasan Industri Makassar - Kanang, Abdul Rahman (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2018)
The central issues in this journal are, how is the implementation of manpower legislation is as the efforts of lawful protection against children workers exploitation and what the obstacles and measures are taken by the government in preventing children workers exploitation. Based on the research results, it can described that the existing lawful protection system for children workers has not been executed in reality; the lawful violations done by the employers do not undergo any lawful actions as they should because the function of manpower supervisory officers is not executed. Therefore, the unity of determination and measure of governmental officers, executive functionaries, businessmen/ employers, parents, and all national components toabolish children workers completely should be striven.